A Comparative Analysis of Gender Concepts: Thought of Nasaruddin Umar and Henri Shalahuddin - Septyayu Catur Pamungkas; Muhammad Ulil Albab; Agus Darwanto (MIZAN: JOURNAL OF ISLAMIC LAW, 2025)
This study examines a conceptual comparison between the idea of Gender Equality, as formulated by Nasaruddin Umar, and Gender Harmony, as articulated by Henri Shalahuddin, within contemporary Indonesian Islamic thought. Both scholars share the same moral vision—to uphold justice and combat gender-based discrimination—yet differ fundamentally in their epistemological and methodological approaches to Islamic teachings. This research uses a qualitative, descriptive, and critical-comparative approach to analyze the primary works of both figures through textual and conceptual study. Nasaruddin Umar represents a reformist-egalitarian paradigm that employs Tawḥīd and Maqāṣid al-sharī‘ah as corrective principles against patriarchal interpretations, emphasizing Qirā’ah Mubādalah to highlight moral and spiritual equality between men and women. Conversely, Henri Shalahuddin stands on a textual-normative foundation that regards revelation (Naṣṣ) and biological nature (fiṭrah) as absolute boundaries, rejecting the notion of absolute equality while proposing Gender Harmony and Mīthāqan Ghalīẓa as the basis for a balanced and just distribution of roles. The findings reveal that both thinkers represent complementary paradigms: Umar focuses on contextual transformation and social justice, while Shalahuddin emphasizes moral stability and natural balance. This dialectic illustrates the dynamic efforts of Indonesian Islamic thought to reconcile modernity and orthodoxy in addressing gender issues. Keywords: Gender Equality; Gender Harmony; Nasaruddin Umar; Henri Shalahuddin; Islamic Gender Thought.